1992
DOI: 10.1002/jsfa.2740600306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short‐term storage on phenolic content, o‐diphenolase and peroxidase activities of cut yam tubers (Dioscorea sp)

Abstract: The effect of short-term storage on the protein, phosphorus and phenolic content as well as peroxidase and o-diphenolase activities of cut, harvested Jamaican yam (Dioscorea sp) tubers (D rofundala, D alata and D cayenensis) was studied. There was an initial increase in the total phenolic content up to the third week of storage followed by a gradual decrease to the sixth week. Phenolic content was found to be highest in D cayenensis followed by D rotundata and D alara. The activities of peroxidase (EC 1 .I1 . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 15 publications
1
13
0
1
Order By: Relevance
“…Increases in total phenols were also reported in different plants after stress conditions such as low temperature storage (Lattanzio et al, 1994) or physical damage (Ke and Saltveit, 1989;Siriphanich and Kader, 1985;Couture et al, 1993). Asemota et al (1992) reported an increase in total phenols in cut yam during 6 wk of storage, followed by a decrease in total phenols, which confirmed results of our study. It was not clear why phenols increased, then decreased substantially during storage.…”
Section: Changes During Storagesupporting
confidence: 94%
“…Increases in total phenols were also reported in different plants after stress conditions such as low temperature storage (Lattanzio et al, 1994) or physical damage (Ke and Saltveit, 1989;Siriphanich and Kader, 1985;Couture et al, 1993). Asemota et al (1992) reported an increase in total phenols in cut yam during 6 wk of storage, followed by a decrease in total phenols, which confirmed results of our study. It was not clear why phenols increased, then decreased substantially during storage.…”
Section: Changes During Storagesupporting
confidence: 94%
“…This reaction is thought to be responsible for the off‐flavours associated with browning and the bitterness of yams when cut, and has been found to exhibit an inhibitory effect on many fungi in vitro 27. High phenolic concentrations would be desirable in tubers at risk of fungal infection, but may be undesirable in tubers for consumption owing to flavour constraints 28…”
Section: Resultsmentioning
confidence: 99%
“…Florido flours had significantly higher sugar content and Omoya the lowest one whereas no significant differences between cultivars were observed for organic acid content. Total phenol content appeared relatively low but was in the range measured on fresh yams: from 0.2 [7] to 30 µM/g (db) for D. rotundata and D. alata species [27,28]. No significant difference was evidenced between the four cultivars.…”
Section: Chemical Characterization Of Yam Flourmentioning
confidence: 91%